2021
DOI: 10.1175/jcli-d-20-0172.1
|View full text |Cite
|
Sign up to set email alerts
|

Autumn Arctic Pacific Sea Ice Dipole as a Source of Predictability for Subsequent Spring Barents Sea Ice Condition

Abstract: This study uses observational and reanalysis datasets in 1980-2016 to show a close connection between a boreal autumn sea-ice dipole in the Arctic Pacific sector and sea-ice anomalies in the Barents Sea (BS) during the following spring. The September-October Arctic Pacific sea-ice dipole variations are highly correlated with the subsequent April-May BS sea-ice variations (r=0.71). The strong connection between the regional sea-ice variabilities across the Arctic uncovers a new source of predictability for spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…The effects of Arctic sea ice on the variability of the stratosphere have been widely explored. Numerous studies revealed that the BKS sea ice variability has more effective impacts on the intensity and location of SPV, and the attendant stratospheric signals can persist for approximately 2 months and then extend to the surface (Jaiser et al., 2013; B. M. Kim et al., 2014; J. Kim & Kim, 2020; Liang Y et al., 2023; Nakamura et al., 2016; Peings & Magnusdottir, 2014; Sun et al., 2015; Wu & Smith, 2016; J. Zhang et al., 2016). Further studies also use a nudging method in modeling to highlight the relative importance of the stratospheric process in Eurasian cooling induced by BKS sea ice loss (Ding et al., 2023; Peings, 2019; Xu et al., 2021, 2023; P. Zhang, Wu, & Smith, 2018; P. Zhang, Wu, Simpson, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of Arctic sea ice on the variability of the stratosphere have been widely explored. Numerous studies revealed that the BKS sea ice variability has more effective impacts on the intensity and location of SPV, and the attendant stratospheric signals can persist for approximately 2 months and then extend to the surface (Jaiser et al., 2013; B. M. Kim et al., 2014; J. Kim & Kim, 2020; Liang Y et al., 2023; Nakamura et al., 2016; Peings & Magnusdottir, 2014; Sun et al., 2015; Wu & Smith, 2016; J. Zhang et al., 2016). Further studies also use a nudging method in modeling to highlight the relative importance of the stratospheric process in Eurasian cooling induced by BKS sea ice loss (Ding et al., 2023; Peings, 2019; Xu et al., 2021, 2023; P. Zhang, Wu, & Smith, 2018; P. Zhang, Wu, Simpson, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is similar spread within more general climate change studies, such as CMIP5 and CMIP6 (Hall et al., 2021; Karpechko et al., 2022). The Arctic represents one source of uncertainty in SPV projections, which could propagate to uncertainty in the surface response (Liang et al., 2023; Zheng et al., 2023). However, few studies have investigated the extent to which model dependency in the SPV response to climate change is driven by model dependency in the response to Arctic climate change specifically.…”
Section: Introductionmentioning
confidence: 99%